Development Not Drug Control: The Evolution of Counter Narcotic Efforts in Thailand. Issue 1 (14th January 2019) - Diskul, M. L. Dispanadda; Ninnad, Ramrada; Skinner, Andrea; Rajatanarvin, Visit-orn
In the 1960s, Thailand was the biggest opium producing country in the world. This article presents Thailand's evolving strategy in solving the problem of illicit poppy cultivation through poverty alleviation and long-term national development. It argues that the root causes of drug crop cultivation and proliferation are poverty, insecurity, and the lack of livelihood opportunities for marginalized communities. Thus, the problem is more a 'development problem' rather than a 'drug problem, ' requiring the addressing of multi-dimensional human development facets in response to the geo-socio-economic conditions of the area. The "Thai approach" is focused on improving the overall w;ell-being of communities, before rule of law can be strengthened, and is very importantly part of long-term broader national development plans. A brief close-up is provided of an example of Thailand's long-term development project, the Doi Tung Development Project, to explain more concretely how Thailand's approach to solve drug crop production translated into practice. Some of these lessons learned from Thailand can and have been shared with the international community in shaping attitudes and policies to drugs and development that are more people-centered, balanced, and sustainable.